Analisis Manajemen Pelayanan Publik Oleh Pemerintah Desa Maria Kecamatan Wawo Kabupaten Bima - Putra Chairil Akbar; Hendra Hendra; Junaidin Junaidin; Arif Budiman; Atun Misnatun (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyse the management of public services at the Maria Village Office, Wawo Sub-district, Bima Regency, with a focus on the application of the principles of public services that are simple, efficient, convenient, and in accordance with statutory provisions. Using a qualitative approach with a case study method, data was collected through interviews, observation, and documentation. The results showed that public services in Maria Village have reflected the principle of simplicity through reasonable fees and sensitivity to community conditions. Adequate office facilities and infrastructure support the effectiveness of services, while the comfort of citizens in dealing with them increases because the process is fast and straightforward. In addition, services have been run in accordance with applicable regulations even though some people do not understand in detail the legal basis. In general, the principle of economy in services has been well implemented, reflected in services that are affordable, efficient, and orientated towards community satisfaction. This research recommends improving the quality of human resources and service systems to strengthen the accountability and transparency of public services at the village level.